Prevalence of symptoms of occupational lung diseases in marble cutting workers - Shrivastava, Ashish; Tomar, Shashi P.; Patel, Mohit (International Journal Of Community Medicine And Public Health, 2018)
Background: Occupational lung diseases occurs in the workers exposed to occupation related hazards. These include Asthma, COPD, Coal worker pneumoconiosis, Silicosis and Asbestosis. Marble cutting exposes workers to fine dust that can cause a number of pulmonary diseases. Usually these are people from rural areas and they are unaware of health hazards related to occupation. Spreading awareness is the key amongst these people. The objective of the To study the prevalence of symptoms related to occupational lung diseases in marble cutting workers, to estimate current status of preventive measures used and to assess adaptive changes after educational interventions Methods: A cross-sectional study was done on the marble cutting workers of Bhedaghat who were exposed to dust from marble cutting. A survey of their working environment and level of awareness was done using questionnaires. The workers were questioned about their working environment, usage of local preventive measures and health related problems. They were then taught about occupational hazards and preventive techniques that can be adopted to prevent such hazards. In subsequent visits, again a survey was done on how many of them were using adaptive measures and relevant counselling was done. Results: Most common reported respiratory problem was shortness of breath 26% and utilization of preventive measures was very poor only 5% but After the 2 follow-up visits including interventional measures and health education, the percentage of workers who started using preventive measures increased from 5% to 57.77%. Conclusions: Prevention is the key to occupational lung diseases. Early diagnosis and treatment also play a major role as prolonged exposure to these risk factors may cause irreversible damage. Health education, periodic health checkups and use to protective measures are the essence in preventing occupational lung diseases.